OSINT Beyond Security Policy - Tampu, Ferenc (Honvédségi Szemle – Hungarian Defence Review, 2025)
The objective of the paper is to give a brief overview of OSINT, which was originally used mainly in military operations in the field of state security intelligence, in light of the literature. First, the concept of information is clarified by illuminating it with concise definitions. Foreign and domestic approaches to the subject are compared in a few words. Some historical examples are given to illustrate OSINT’s use in the past and its application in different fields and periods. The importance of OSINT extends beyond its everyday use, as evidenced by the fact that it is still used today by governmental bodies, in security policy, from the civilian sector to marketing. The World Wide Web and social media have brought radical changes. They have transformed the way we search for information and the tools we use. At the same time, the development of information technology has seen unprecedented progress. This is why both computers and artificial intelligence have been put at the service of open-source intelligence. The paper considers both the advantages and disadvantages of OSINT and reflects on legal and ethical issues, providing a background knowledge of the law.